Stable isotope ratios of H, C, O, N and S for the geographical traceability of Italian rainbow trout (Oncorhynchus mykiss). (30th November 2018) - Camin, Federica; Perini, Matteo; Bontempo, Luana; Galeotti, Marco; Tibaldi, Emilio; Piasentier, Edi
Highlights: 130 rainbow trout reared in 20 Italian farms with high or low fish content. The C, N, S isotope ratios of feed and fillet are highly positively correlated. The H, O ratios of fillet are positively interrelated with the O ratio of tank water. 91% of correct classification was obtained by PLS-DA for two Italian regions. Abstract: Multielement isotope ratio was assessed in fat and defatted (protein) fillet of 130 rainbow trout, reared with feed incorporating a high or low fish content in 20 Italian farms, focusing on two northern Italian regions (Friuli Venezia Giulia and Trentino). The aim was to investigate the ability of isotopic analysis to trace the geographical origin of trout, also according to the type of feed. The carbon, nitrogen and sulphur isotope ratios of feed and fillet were highly positively correlated both within each matrix (feed or fillet) and between the two matrices and negatively correlated with the δ 2 H and δ 18 O of feed and the δ 2 Hfat . The δ 2 Hprotein and δ 18 Oprotein were positively interrelated with the δ 18 O of tank water. By applying the tested Partial Least Squares – Discriminant Analysis multiclass model (85 fillets) to the validation dataset (45 fillets), 91% accuracy was obtained for the two Italian regions.